O neuromarketing eleitoral digital e a preservação da liberdade de sufrágio: uma análise à luz da Constituição Federal de 1988 e da LGPD. - Rodrigues, Matheus Barbosa (2022)
The dissertation had the general objective of analyzing the technique of electoral neuromarketing in the context of constitutional norms and national privacy protection, aiming to answer the following research question: does electoral neuromarketing violate freedom of suffrage? To this end, the following specific objectives were set: to analyze neuropolitics as a phenomenon connected to neuromarketing, to define the latter, to present its instrumentalization tools, possible problems when in contrast to rational political choice and its electoral impact. Also, the rights affected by neuromarketing will be examined, namely, the rights to citizenship, privacy, vote secrecy and freedom of suffrage, as set forth in the Federal Constitution of 1988. Afterwards, in what was called the infraconstitutional core of the dissertation, research was carried out on informational self-determination and the free development of the personality, as defined in the General Data Protection Law, in addition to the right to electoral propaganda under the terms of Law n° 9.504/97 and Resolution n° 23.610/2019, of the Superior Electoral Court, in what it regulates electoral propaganda. Subsequently, confronting neuromarketing with fundamental political rights, regulatory parameters applicable to neuromarketing were presented, in addition to, also based on the Civil Procedure Code, proposing ways to correct possible abuses committed in the placement of electoral propaganda. Further on, the role of subnational tutelages in the preservation of freedom of suffrage was briefly examined, especially in light of the constitutional division of competences. In the end, it was found that electoral neuromarketing, in the way it is currently practiced, is unconstitutional and illegal, as it violates freedom of suffrage, in addition to the rights to vote secrecy, privacy and data protection, citizenship, self-determination, information and the free development of personality.